Durability-enhanced vanadium dioxide thermochromic film for smart windows. (June 2020) - Zhao, X.P.; Mofid, S.A.; Gao, T.; Tan, G.; Jelle, B.P.; Yin, X.B.; Yang, R.G.
Abstract: Vanadium dioxide (VO2 )–based thermochromic films are of great interest for energy-saving smart windows as they can dynamically change the solar transmittance as the ambient temperature changes. However, VO2 is thermodynamically unstable and could be easily oxidized by the oxygen and moisture in the ambient air. In this work, a durability-enhanced VO2 nanoparticle-polymer thermochromic film was proposed and fabricated using the blade coating method where the cross-linked and highly entangled poly(methyl methacrylate) (PMMA) chains with a molecular weight (~ 950, 000) was adopted to block gas diffusion in the polymer matrix. It was shown that the developed VO2 nanoparticle film kept ~30% of its solar modulation ability after ~900 h of accelerated durability test in the aging environment with a temperature at 60 °C and ~95% relative humidity. This is ~4 times of the lifetime of the VO2 nanoparticles which are embedded in the non–cross-linked PMMA matrix with low molecular weight (~15, 000). The cross-linked PMMA-VO2 film also showed a high luminous transmittance of ~50%, a high solar modulation ability of ~17%, and a low haze of ~11%. Our method provides an easy and effective strategy to improve the lifetime of VO2 nanoparticles, showing a promising pathway toward environmentally stable and easily scalable thermochromic films for energy-efficient smart windows. Graphical abstract: Image 1 Highlights: The highly entangled and cross-linked poly(methyl methacrylate) (PMMA) matrix was used to improve the lifetime of vanadium dioxide (VO2 ) nanoparticles. The PMMA-VO2 thermochromic film shows a high luminous transmittance of ~50% and solar modulation ability of ~17%. No noticeable decay of the solar modulation ability was observed after ~3000 cycles of the fatigue test. The proposed method provides a promising pathway toward environmentally stable and easily scalable thermochromic film.